Classifying cesarean section using Robson Classification: An Indonesian tertiary hospital survey - Ali Sungkar; Budi Iman Santoso; Raymond Surya; Adly NA Fattah (Majalah Obstetri dan Ginekologi, 2019)
Objectives: Cesarean delivery rates have increased remarkably and cause a major public health concern. This study aims to evaluate the feasibility of using the Robson Ten Group Classification System (TGCS) for cesarean delivery (CD) indications at institutional level.Materials and Methods: Database of all women delivering at Cipto Mangunkusumo Hospital, Jakarta, Indonesia were analayzed. The CD rates overall and in each Robson group were calculated, as was the contribution of each group to the overall CD rate. In addition, the CD indications in each group were analyzed.Results: Approximately almost half (48.04%) of women delivered by CS in our study. Groups 10 was the largest groups representing 27.82% of the obstetric population. The second and third largest were group 3 and 1, which represents 18.00% and 17.34%, respectively. The highest relatively contribution of CS rate were group 10, 1, and 3 with the percentage of 28.24%, 17.59%, and 15.19%; contributively.Conclusion: The TGCS can be applied at institutional level. It helps in planning strategies for specific subgroups of women to reduce CS rate and improve outcomes.